Leveraging the Potential of In Situ Green-Synthesized Zero-Valent Iron Nanoparticles (nZVI) for Advanced Oxidation of Clinical Dyes in Water - María F. Alexandre-Franco; Cristina Rodríguez-Rasero; Ana González-Trejo; Mireya Casas-Pulido; Carmen Fernández-González; Eduardo M. Cuerda-Correa (Applied Sciences, 2024)
Nanotechnology, a rapidly growing field, holds tremendous promise as it harnesses the unique properties and applications of nanoparticulate materials on a nanoscale. In parallel, the pressing global environmental concerns call for the development of sustainable chemical processes and the creation of new materials through eco-friendly synthesis methods. In this work, zero-valent iron nanoparticles (nZVI) were synthesized using an innovative and environmentally friendly approach as an alternative to conventional methods. This method leverages the antioxidant capacity of natural plant extracts to effectively reduce dissolved metals and produce nZVI. The chosen extract of green tea plays a pivotal role in this process. With the extract in focus, this study delves into the remarkable capability of nZVI in degrading two dyes commonly used in medicine, chrysoidine G and methylene blue, in aqueous solutions. Additionally, Fenton-type oxidation processes are explored by incorporating hydrogen peroxide into the nanoparticle mixture. By applying the statistical design of experiments and Response Surface Methodology, the influence of four key parameters—initial concentrations of Fe2+, Fe3+, H2O2, and polyphenols—on dye elimination efficiency in aqueous solutions is thoroughly analyzed. The obtained results demonstrate that advanced oxidation technologies, such as Fenton-type reactions in conjunction with nanoparticles, achieve an excellent efficiency of nearly 100% in eliminating the dyes. Moreover, this study reveals the synergistic effect achieved by simultaneously employing nZVI and the Fenton process, showcasing the potential for further advancements in the field.